A 400MHz Single‐Chip CMOS Transceiver for Long Range High Definition Video Transmission in UAV Application. Issue 3 (1st May 2020) - Huang, Shuigen; Lin, Min; Wang, Ruoyu; Chen, Zhuojun; Dong, Yemin
Abstract : A fully‐integrated 400MHz transceiver for high definition video transmission in Unmanned aerial vehicle (UAV) is presented. The transceiver integrates a Receiver (RX), a Transmitter (TX), a tunable multi‐mode complex filter, two sigma‐delta fractional‐N PLL frequency synthesizers and some baseband calibration circuits, which is applicable for both Time division duplex (TDD) and Frequency division duplex (FDD) systems. In order to meet different data rate and sensitivity requirements for control signal and video signal transmission, the transceiver supports BPSK/QPSK/QAM modulation. The receiver sensitivity is ‐75dBm and the transmitter provides emission power up to 12dBm. Besides, the Error vector magnitude (EVM) of ‐35dB is measured under 64QAM modulation with 54Mbps data rate. Fabricated in a standard 130nm CMOS process and operated at 1.2V supply for most circuits excluding PA, 3.3V supply for PA, the receiver and the transmitter consume 68.2mW and 164.3mW, including the frequency synthesizer, respectively. The total chip area with pads is 6.25mm 2 .